Innovative endpoint determination system for antifungal susceptibility testing of yeasts. - Tellier, R (1992)
Fungal infections and antifungal resistance are increasingly recognized. Antifungal susceptibility testing remains unstandardized, and a particularly important problem is endpoint determination. In this paper we propose the yeast metabolic reduction of the tetrazolium salt 2,3-bis(2- methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)carbonyl]-2H-tetraz olium hydroxide (XTT) as a colorimetric endpoint which is quantitative and objective. Amphotericin B, fluorocytosine, and fluconazole dose-response curves were obtained, and a metabolic MIC could be determined by using precise criteria.